HOSPITAL CLOWNING IN THE RESOCIALIZATION OF ADOLESCENT GIRLS AND YOUTH WITH HEALTH RESTRICTIONS - Semenova, Elena (Revista Inclusiones, 2020)
The article examines anorexia nervosa and bulimia as prerequisites for the formation of multiple health restrictions. The author focuses on the cases of the development of anorexia nervosa and bulimia provoked by the person’s desire to identify with an artistic image resulting in the person finding themselves in a difficult life situation with the desire and ability to abandon the identification with an artistic image is temporarily lost. The impact of artistic image on personality is examined on the example of a biographical portrait of a young woman with progressive schizophrenia suffering from vomitomania, as well as on the example of a bulimic path of anorexia nervosa development (without brain pathologies) in young women with experience in performing and theatrical activities and the members of online communities consolidating around the images of anorexic beauty, promoting the superiority of this lifestyle of a person with special health needs, and encouraging the use of diuretics, laxatives, regular stomach cleansing procedures, etc. It is concluded that, along with the widespread belief that young women seek to imitate feminine images cultivated in society, anorexic and bulimic behavior can be found to be a signal of the lack of societal demand for their androgynous, tricksterlike, comic female nature and the resistance against the recognized “Barbie standards”.